Role of knowledge sharing and learning process of students - Sutharsini, J.; Umakanth, N.; Sabina, D. (University of Jaffna, 2021)
Knowledge sharing among peers plays a vital role in students’learning process and an Effective and inclusive Knowledge Sharing is an integral part of successful and practical university learning. This study aims to investigate the knowledge- sharing behavior of undergraduate students of the Faculty of Management Studies and Commerce students at the University of Jaffna. The present study involved a quantitative approach concerning the design of surveys and the population to reach that purpose. The researcher used SPSS software version 20.0 for data analysis purposes. It was found that, generally, students displayed a positive attitude towards knowledge sharing and were appreciative of its importance in peer learning. It was found that, generally, students displayed a positive attitude towards knowledge sharing and were appreciative of its importance in peer learning. Further, the study found that technological availability, social media ties, self-efficacy, and experience were the significant determinants of knowledge-sharing behavior among students. Final recommendations are given by the author; it also provides more support and direction to future work.
Keywords: Higher Education; Knowledge sharing behavior; Knowledge; Student’s learning; University of Jaffna